(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The article presents the experience of Tormenta de Lagartos, in relation to the creation of its latest show "La Chupósfera", which navigated the state prior to the health emergency, traveling through virtual space, isolation, relationship with restrictions and how we got to the present. Questions and reflections are formulated, in addition to sharing our theater of dolls, masks and animated shapes and our method of writing and recording through the so-called "logbook" (Bitácoras)